Enhancement of the cooling performance of an electrical power transformer using geometrical parameters - Hashim, Marwa Mohammed; Basher, Hadi O. (Al-Qadisiyah journal for engineering science, 2025)
This study investigates the influence of electrical transformer shape and fin configuration on the cooling process, emphasizing performance under varying ambient temperatures. Cooling efficiency is critical for transformer reliability, longevity, and operational safety. Traditional transformer shapes often face limitations in heat dissipation, leading to potential hotspots that can affect performance. This research utilized numerical simulations and experimental validation to compare various transformer shapes and fin configurations, focusing particularly on a 250 KVA Oil Natural Air Natural (ONAN) type transformer designed with real-world specifications. Key findings indicated that a hexagonal transformer shape and zigzag-shaped fins with rib configurations spaced at 7 cm intervals provided superior cooling efficiency. This optimized design resulted in a maximum stable temperature of approximately 332.31 K, significantly lower than that observed in traditional rectangular designs. The zigzag fins increased the effective surface area for heat dissipation, facilitating improved thermal performance. Numerical analysis using ANSYS Fluent demonstrated enhanced coolant flow and uniform pressure distribution, with higher coolant velocity reaching 0.252 m/s. This uniformity mitigated potential hotspots and mechanical stress, contributing to overall structural integrity. Experimental validation was conducted under Iraqi weather conditions, reinforcing the numerical results. Temperature tests confirmed that the optimized hexagonal design consistently maintained lower oil and component temperatures than traditional shapes. This study used Finite Element Analysis (FEA) to investigate the impact of changes in geometrical parameters. A theoretical approach based on classical mechanics was applied, where force distribution was modeled using elasticity theory. The percentage difference represents 5.26% of Coil temperature, 5.1% of Oil temperature, and 5.25 % of fins temperature, where the percentage difference represents 1.52% of all coil temperature, comparing the optimum case with previous research with experimental tests.